2016
DOI: 10.1111/sjop.12331
|View full text |Cite
|
Sign up to set email alerts
|

Ability emotional intelligence and its relation to aggression across time and age groups

Abstract: Emotional Intelligence (EI) has been associated with several indicators of psychosocial adjustment, including aggressive behavior, but the relevant research has been mostly cross-sectional, focused on adults, and limited to trait EI measures (García-Sancho, Salguero & Fernández-Berrocal, 2014; Mayer, Roberts & Barsade, ). The present work explored the relationship between Ability Emotional Intelligence (AEI) and aggression in both adults and adolescents using cross-sectional and longitudinal designs. We conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 51 publications
(75 reference statements)
4
28
0
7
Order By: Relevance
“…Our data support the sequence of change in our outcomes, allowing advancement in the understanding of complex relations among cognitive/emotional processes in aggression compared to prior research with shorter term interventions (Castillo et al., ; Durlak et al., ) or cross‐sectional data (García‐Sancho et al., ; Mayer et al., ). Furthermore, our results are consistent with recent findings that support emotional intelligence abilities as predictors of some of the variance in aggressive behavior among adolescents through a longitudinal design (9 months later; García‐Sancho et al., ). Furthermore, this study makes an important contribution to the existing literature supporting the role that emotional abilities play in the prevention of aggressive manifestations with a superior longitudinal design of three consecutive academic years.…”
Section: Discussionsupporting
confidence: 92%
“…Our data support the sequence of change in our outcomes, allowing advancement in the understanding of complex relations among cognitive/emotional processes in aggression compared to prior research with shorter term interventions (Castillo et al., ; Durlak et al., ) or cross‐sectional data (García‐Sancho et al., ; Mayer et al., ). Furthermore, our results are consistent with recent findings that support emotional intelligence abilities as predictors of some of the variance in aggressive behavior among adolescents through a longitudinal design (9 months later; García‐Sancho et al., ). Furthermore, this study makes an important contribution to the existing literature supporting the role that emotional abilities play in the prevention of aggressive manifestations with a superior longitudinal design of three consecutive academic years.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning our second objective, the results demonstrated significant negative correlations between AEI with physical, verbal, and indirect aggression, which corroborates previous findings showing similar magnitude of correlations, with higher associations between AEI and physical and indirect than verbal aggression (García‐Sancho et al ., , ). Moving beyond previous research, our results revealed that high AEI can also buffer against the effects of anger on aggression.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have shown that people with higher AEI are less likely to engage in aggressive behavior than people with lower AEI (García‐Sancho, Salguero & Fernández‐Berrocal, ). This negative relationship was found in three types of aggression: physical, verbal, and indirect in cross‐sectional and longitudinal studies and the associations was stronger with physical than verbal and indirect aggression (García‐Sancho, Salguero & Fernández‐Berrocal, ; García‐Sancho, Salguero & Fernández‐Berrocal, ). AEI has also been shown to be negatively associated with anger rumination (García‐Sancho et al ., ).…”
Section: Emotional Intelligence As Moderator In the Relationship Betwmentioning
confidence: 97%
See 1 more Smart Citation
“…Ability Emotional Intelligence juga turut menyumbang muncul dan meningkatnya perilaku agresi siswa (García-Sancho, Salguero, & Fernández-Berrocal, 2017). Menurut penelitian lain, emotional self-efficacy juga turut menyumbang pada munculnya perilaku agresi siswa (Valois, Zullig, & Revels, 2017).…”
Section: Pembahasan Tingkat Agresi Berdasarkan Jenis Kelaminunclassified